Novel Heterometallic Lanthanide Complex Using Cobalt Tripod Ligands: Synthesis, Crystal Structure Analysis, and Magnetic and Proton Conduction Behavior. (2nd October 2020) - Song, Jeong Hwa; Lee, Giseong; Lee, Woo Ram; Lim, Kwang Soo
Abstract : A 3d‐4f heterometallic cobalt(III)‐cerium(III) sandwich complex was successfully synthesized and its properties were analyzed. The structure of 1 was specifically analyzed by single crystal X‐ray diffraction analysis, and structural simulations were performed based on single crystal X‐ray diffraction data. We were able to observe changes in the structure of this complex accompanied by changes in proton conduction properties according to temperature and humidity conditions, indicating that the structure influences the formation of the proton conduction pathway. In addition, it was confirmed by measurement that this complex also exhibited magnetic behavior.